2022
DOI: 10.5688/ajpe8606
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Association of Altmetric Attention Scores With Citations in Selected Major Pharmacy Journals

Abstract: Objective. To determine the long-term change in the Altmetric Attention Score (AAS), and its components, as well as the impact of higher AAS on citation count for articles published in major pharmacy journals. Methods. This study evaluated articles from pharmacy journals ranked in the top 10% according to their AAS in the year 2017. Correlation between the AAS and number of citations (through November 2020) was assessed using the Spearman's correlation test. A Kruskal-Wallis 1-way analysis of variance was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The relationship between the Altmetric scores and citation counts has been investigated in different studies. Some of them have found a significant association between these two variables in some academic fields, such as pharmacy (Dixon & Baker, 2022), and some have not found such a relationship in other fields like dermatology (Nip & Feng, 2022). This study found no significant association between Altmetric score and citation count in the journalism subject area.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the Altmetric scores and citation counts has been investigated in different studies. Some of them have found a significant association between these two variables in some academic fields, such as pharmacy (Dixon & Baker, 2022), and some have not found such a relationship in other fields like dermatology (Nip & Feng, 2022). This study found no significant association between Altmetric score and citation count in the journalism subject area.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, publishers and researchers can keep track of where their scientific work has been shared and discussed among broader audiences by using the AAS 2 . An increasing number of journals have also embraced AAS to promote themselves 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 An increasing number of journals have also embraced AAS to promote themselves. 3,4 AAS is mainly based on online mentions and weighted composite scores including online platforms such as Twitter/X, Facebook, Reddit, YouTube, LinkedIn, Google þ , Research highlight form, Wikipedia, patent, Policy Source, blogs, and news outlet in increasing emphasis factor (0.25-8). 1,5 The exact way AAS is calculated is unknown, making it impossible for an individual to recalculate the index.…”
Section: Introductionmentioning
confidence: 99%
“…It would take time to accumulate citation times [10], and diferent journal articles could not be compared directly even in the same research feld [11,12]. Absolute citation times favor older journal articles and have limited utility in comparing journal articles from diferent felds [12,13]. Tus, new metrics have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of digital technology and the use of online platforms to discuss research, alternative-level metrics (altmetrics) have been introduced in research felds [12][13][14]. Tey were used to measure the journal articles with attention, dissemination, overall infuence, and impacts [14].…”
Section: Introductionmentioning
confidence: 99%